DIPG-18. SONIC HEDGEHOG (SHH) SIGNALLING PROMOTES BLOOD BRAIN BARRIER (BBB) INTEGRITY IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) - Sajesh, Babu (Neuro Oncol, 2019)
DIPG is the most common brainstem tumor in children and is uniformly fatal. The BBB is intact in DIPG and plays an active role in restricting the delivery of systemically administered therapies into the tumor. Recent studies have shown that SHH signalling plays a major role in the maintenance of BBB integrity and this pathway is highly active in DIPG. We hypothesized that SHH signalling in DIPG plays a critical role in maintaining BBB integrity. Primary DIPG PDX (patient derived xenografts) secretes significantly higher quantities (~2-fold) of SHH compared to astrocytes and human brain microvascular endothelial cells (hBMVECs), (ELISA, P-value <0.0001). SHH and its pathway members were significantly higher in DIPG cells (>750-fold increase in mRNA) when compared to astrocytes or endothelial cells, (qRT-PCR, P-value <0.0001). Western blot analyses of PDX showed increased expression of SHH when compared to controls and was confirmed in a cohort of 5 postmortem tumor samples by immunohistochemistry. In vitro analyses showed that hBMVECs treated with DIPG tumor-conditioned media significantly increased trans-endothelial electrical impedance (TEER) and decreased permeability to both low (NaFl) and high molecular weight (IR dye PEG 800) compounds, suggesting increased barrier properties. These results were also corroborated using SHH pathway agonists, while the antagonists decreased TEER/permeability. We will present data of ongoing in vivo studies of BBB permeability in an orthotopic DIPG tumor model using PDX and SHH antagonists (Vismodegib, PF5274857 hydrochloride). Our results suggest that SHH pathway is integral to BBB integrity in DIPG tumors and pharmacological inhibition of the SHH pathway may disrupt the BBB and improve the delivery of therapeutic agents in the treatment of DIPG.